2016
DOI: 10.1002/2016gl069452
|View full text |Cite
|
Sign up to set email alerts
|

Structure II gas hydrates found below the bottom‐simulating reflector

Abstract: Gas hydrates are a major component in the organic carbon cycle. Their stability is controlled by temperature, pressure, water chemistry, and gas composition. The bottom‐simulating reflector (BSR) is the primary seismic indicator of the base of hydrate stability in continental margins. Here we use seismic, well log, and core data from the convergent margin offshore NW Borneo to demonstrate that the BSR does not always represent the base of hydrate stability and can instead approximate the boundary between struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 75 publications
(125 reference statements)
3
39
0
Order By: Relevance
“…However, at structurally controlled systems with high‐methane flux (e.g., Hydrate Ridge) drilling through the BSR has shown that the BSR does coincide with the predicted BGHS [ Trehu et al ., ]. Similarly, a recent study from borehole data at thermogenic gas hydrate systems of the convergent margin of Borneo documents a BSR that coincides with the BGHS predicted for measured concentrations of >96% methane type II gas hydrates [ Paganoni et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at structurally controlled systems with high‐methane flux (e.g., Hydrate Ridge) drilling through the BSR has shown that the BSR does coincide with the predicted BGHS [ Trehu et al ., ]. Similarly, a recent study from borehole data at thermogenic gas hydrate systems of the convergent margin of Borneo documents a BSR that coincides with the BGHS predicted for measured concentrations of >96% methane type II gas hydrates [ Paganoni et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of >5% ethane and other higher‐order hydrocarbons as well as methane carbon isotopic ratios of ~40 ‰ point toward a significant contribution of thermogenic gas sources at Vestnesa Ridge (Figure ) [ Paull and Ussler , ]. Even with the abundant C 2 + measured though, these samples collected near the seafloor (<6 m bsf) along Vestnesa Ridge (Table ) are likely to underestimate the contribution of higher‐order hydrocarbons in the hydrate system at greater depths (within 140–190 m bsf), as recently documented from borehole data at the margins of Borneo [ Paganoni et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the term BGHSZ is to be interpreted as base of structure I gas hydrate, or in line with previous suggested terminology, BS I GHSZ [e.g., Boswell et al, 2016;Paganoni et al, 2016]. We further want to emphasize that our study is not concerning the detailed and local gas hydrate concentrations with depth and any localized variations therein.…”
Section: 1002/2017gc006805mentioning
confidence: 99%
“…6. Borneo (passive continental margin) i. Gumusut drilling project [Paganoni et al, 2016] [Suess et al, 1988]. 8.…”
Section: Introductionmentioning
confidence: 99%